Kedudukan Hadis dan Istinbath Hukum Lembaga Bahtsul Mas’ail Nahdlatul Ulama - Agus Faisal Asyha (Journal Khafi : Journal Of Islamic Studies, 2023)
The Koran and Hadith as the main sources of Islamic law are limited in number, but the things that arise in life are complex and unlimited. To deal with problems that are more complicated and full of novelty, sometimes there are no specific laws in the Koran and Hadith, so ijtihad is needed for this situation. Through the Bahtsul Masail forum, Nahdlatul Ulama always actively schedule discussions about actual problems by optimally trying to solve the deadlock in Islamic law resulting from the continuous social development of society without knowing boundaries, while textually there is no basis for it in the Qur'an. and Hadith, or there is a basis for it but the expression is not clear. Therefore, the Bathsul Masail institution must have a method for carrying out ijtihad. The Legal Istinbath Methodology of the Bahtsul Masail Nahdlatul Ulama Institute has three method approaches arranged hierarchically, namely the qauli method approach, the ilhaqi method, and the manhaji method. However, to answer various concerns regarding the absence of an operational method of legal istinbat, and one that can represent the model of the manhaji school of thought, Nahdlatul Ulama at its 33rd Congress in 2015, through the Bahtsul Masail al-Diniyyah al-Maudu'iyyah Commission formulated a method of istinbat al-ahkam . Operationally it is structured into three methods, namely the bayani method, the qiyasi method, and the istislahi or maqasidi method.